ChemInform Abstract: CaYGaO4; a Fully Ordered Novel Olivine Type Gallate. Issue 44 (4th November 2014) - Clark, Ryan; Zhu, Sarah Jiaxin; Zheng, Shou‐Tian; Bu, Xianhui; Derakhshan, Shahab
Abstract The title compound is prepared by solid state reaction of stoichiometric amounts of Y2O3, CaCO3, and Ga2O3 (900 °C for 24 h and 1250 °C for 48 h).